2012
DOI: 10.1371/journal.pone.0036413
|View full text |Cite
|
Sign up to set email alerts
|

Mifepristone Increases the Cytotoxicity of Uterine Natural Killer Cells by Acting as a Glucocorticoid Antagonist via ERK Activation

Abstract: BackgroundMifepristone (RU486), a potent antagonist of progesterone and glucocorticoids, is involved in immune regulation. Our previous studies demonstrated that mifepristone directly augments the cytotoxicity of human uterine natural killer (uNK) cells. However, the mechanism responsible for this increase in cytotoxicity is not known. Here, we explored whether the increased cytotoxicity in uNK cells produced by mifepristone is due to either anti-progesterone or anti-glucocorticoid activity, and also investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 55 publications
4
22
0
Order By: Relevance
“…These cells possess a unique receptor phenotype with latent cytotoxicity and produce various cytokines that are essential for survival of the fetus. Previous studies have demonstrated that although uNK cells are beneficial in regulating normal pregnancy, they can be transformed into detrimental cells in response to bacterial and viral infections . The LPS‐treated pregnant mice exhibited a significant decrease in the number of uNK cells, as well as a significant increase in the number of uterine pro‐inflammatory neutrophils .…”
Section: Discussionmentioning
confidence: 91%
“…These cells possess a unique receptor phenotype with latent cytotoxicity and produce various cytokines that are essential for survival of the fetus. Previous studies have demonstrated that although uNK cells are beneficial in regulating normal pregnancy, they can be transformed into detrimental cells in response to bacterial and viral infections . The LPS‐treated pregnant mice exhibited a significant decrease in the number of uNK cells, as well as a significant increase in the number of uterine pro‐inflammatory neutrophils .…”
Section: Discussionmentioning
confidence: 91%
“…During early pregnancy, uNK cells regulate trophoblast invasion and the vascular changes that support placental development. uNK cells express GR, and uNK cell-mediated cytotoxicity is sensitive cortisol treatment [82, 83]. Prednisolone treatment in women with recurrent miscarriage is associated with reduced numbers of uNK cells, although a link between the glucocorticoid-mediated reduction in uNK cell numbers and pregnancy success was not demonstrated [84].…”
Section: Reproductive Immunology: Immuno-modulatory Actions Of Glucocmentioning
confidence: 99%
“…The authors observed decreased mRNA levels of the enzyme 11 β HSD1 in ESC decidualized in vitro , which is consistent with the increased presence of CD56 + cells in the corresponding tissue. This enzyme is involved in the synthesis of cortisol, a potent inhibitor of uNK cell cytotoxicity [ 184 ]. Hence, it is possible that cortisol deprivation caused by 11 β HSD1 insufficiency in the stromal cells leads to the enrichment of activated NK cells, linked to low fertility status of the patients.…”
Section: Dsc Involvement In Reproductive Pathological Conditionsmentioning
confidence: 99%